Model Integrasi Nilai Islam Dalam Pembelajaran oleh Mahasiswa Calon Guru SD: Studi Analisis Modul Ajar - Azhar Syarifuddin; Ahmad Rif'an Najih; Rizky Dzawata Afnani (STKIP AL HIKMAH SURABAYA, 2025)
The integration of Islamic values in learning is an essential requirement for prospective elementary school teachers in promoting value-based education. This study aims to analyze the level and models of Islamic value integration in teaching modules developed by prospective elementary school teachers. The study employed a qualitative approach using content analysis of five student-developed teaching modules. Data were analyzed using an Islamic value integration rubric encompassing four aspects: learning objectives, learning materials, learning activities, and learning assessment, which were further classified into implicit, explicit, and contextual integration models. The findings indicate that all teaching modules contained elements of Islamic value integration; however, the integration was not implemented comprehensively or systematically. Islamic values were most dominantly integrated into learning activities, while learning objectives and assessment components demonstrated a low level of integration. The implicit integration model was the most frequently used, followed by explicit and contextual models, suggesting that Islamic values tend to be positioned as supporting elements rather than as core pedagogical foundations. These findings reveal a gap between students’ normative understanding of the importance of Islamic values and their ability to translate these values into coherent instructional planning. This study recommends strengthening pedagogical training in teacher education institutions to enable prospective teachers to design holistic and meaningful Islamic value-based learning in elementary education.